Interactive Games as Tools for Health Education in Children: A Systematic Review - Lina Handayani; Nur Afriza; Tria Nisa Novianti (Jurnal Berkala Kesehatan, 2025)
Interactive games are increasingly used in early childhood health education for their ability to merge learning with play. This systematic review evaluated the effectiveness of interactive games in improving health literacy and behaviors among children aged 4–12 years. A systematic search was conducted in accordance with PRISMA 2020 guidelines. Of 312 records, 20 met inclusion criteria and were appraised using the Joanna Briggs Institute tool. Studies, originating from the US, Greece, Indonesia, Malaysia, and Brazil, examined digital games (n=12), board games (n=5), and role-play simulations (n=3) targeting personal hygiene, nutrition, physical activity, and emotional health. Seventy-five percent reported significant improvements in knowledge, and 60% documented positive behavioral changes at short-term follow-up. Common benefits included increased engagement (85% of studies) and enhanced socio-emotional skills. Study quality was mostly moderate; few included follow-up beyond six months. Interactive games show strong potential to enhance children’s health education, but technological access and lack of long-term evaluation remain barriers. Future work should focus on high-quality, longitudinal studies and integration into school and community health programs.